177k views
9 votes
Complete the table by writing the product of each expression. (Show work below)

Complete the table by writing the product of each expression. (Show work below)-example-1

1 Answer

9 votes

Answer:

a. Convert to improper fraction first:

-2⁴/₉ = -24/9

= -24/9 * 1/2 = -24/18 = -4/3

= -1¹/₃

b. -2/3 * 1/4 = -2/12

= -1/6

c. Convert to improper fraction:

= -1¹/₂ = -3/2

= -3/2 * -1/6

= 3/12

= 1/4

d. Convert to improper fraction:

= 2¹/₃ = 7/3

= 1/6 * 7/3

= 7/18

User Thilak
by
5.6k points